Functional independence of elderly patients who fell: a follow-up study - Guilherme Guarino de Moura Sá; Ana Maria Ribeiro dos Santos (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to evaluate, in emergency hospital service and at home, the functional independence of elderly people who fell. Method: longitudinal study with 151 elderly. Functional Independence Measure (FIM) was used. Statistical tests were performed with univariate and bivariate analysis. Results: mean of total FIM value in the hospital was 70.4; and at home 84.3 (p <0.001). Independence was lower in the motor domain, in "self-care", "mobility" and "locomotion" dimensions, in the two evaluations (p <0.001). Dependence reduced from 97.3% elderly in the hospital to 82.8% at home (p <0.001). There was a negative correlation between total FIM and age, number of medications, number of diseases and hospitalization time in both evaluations. Femoral and hip fractures were associated with lower total FIM values (p <0.001). Conclusion: the elderly had less independence in the hospital compared to at home, with greater impairment in the motor domain and "self-care", "mobility" and "locomotion" dimensions, in the two moments evaluated.